Suicide plus immune gene therapy prevents post-surgical local relapse and increases overall survival in an aggressive mouse melanoma setting - Villaverde, Marcela Solange (2014)
In an aggressive B16-F10 murine melanoma model, we evaluated the effectiveness and antitumor mechanisms triggered by a surgery adjuvant treatment that combined a local suicide gene therapy (SG) with a subcutaneous genetic vaccine (Vx) composed by B16-F10 cell extracts and lipoplexes carrying the genes of human interleukin-2 and murine granulocyte and macrophage colony stimulating factor. Pre-surgical SG treatment, neither alone nor combined with Vx was able to slow down the fast evolution of this tumor. After surgery, both SG and SG+Vx treatments, significantly prevented (in 50 % of mice) or delayed (in the remaining 50 %) post-surgical recurrence, as well as significantly prolonged recurrence-free (SG and SG+Vx) and overall median survival (SG+Vx). The treatment induced the generation of a pseudocapsule wrapping and separating the tumor from surrounding host tissue. Both, SG and the subcutaneous Vx, induced this envelope that was absent in the control group. On the other hand, PET scan imaging of SG+Vx group suggested the development of an effective systemic immunostimulation that enhanced 18FDG accrual in thymus, spleen and vertebral column. When combined to surgery, direct intralesional injection of suicide gene plus distal subcutaneous genetic vaccine displayed efficacy and systemic antitumor immune response without host toxicity. This suggests the potential value of the assayed approach for clinical purposes.